GSA dengan Skrining Faktor untuk Evaluasi Kinerja Relai Proteksi Saluran - Nanang Rohadi; Bambang Mukti Wibawa; Nendi Suhendi (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2024)
This paper presents a global sensitivity analysis with factor screening to efficiently test conventional distance relay algorithm models used as transmission line protection devices with series compensators. Various system indeterminacy parameters (factors) may affect the functional performance of the fault impedance measurement algorithm model of intelligent electronic devices, specifically the SEL-421 type distance relays. The purpose of global sensitivity testing is to determine the influence strength of individual and interacting factors on the output of the fault impedance measurement algorithm. Global sensitivity analysis, conducted through variance analysis using quasi-Monte Carlo methods, aims to compute the error in fault impedance measurement results. As an initial step, the Morris method was employed to filter out factors that did not predominantly affect relay performance, thereby reducing the computational burden of the global sensitivity analysis. Several simulated transmission line faults with series compensators and multiple factors were modeled using DIgSILENT PowerFactory. Automatic fault simulations, both before and after compensators, were developed using DIgSILENT Programming Language. The sensitivity of the relay algorithm output was tested for each simulation based on read-out voltage, fault current signals, and the values of sampled factors using both Morris and Sobol methods. The variance of the algorithm output model influenced by several factors was calculated using SIMLAB software. Fault resistance emerged as the dominant factor affecting algorithm performance, with sensitivity indices exceeding 0.9 and 0.7 for faults before and after the compensator, respectively. This technique has effectively tested the SEL-421 distance relay algorithm.